Effects of peripheral inflammation on the blood-spinal cord barrier - Xanthos Dimitris N; Püngel Isabella; Wunderbaldinger Gabriele; Sandkühler Jürgen (SAGE Publishing, 2012)
Abstract Background Changes in the blood-central nervous system barriers occur under pathological conditions including inflammation and contribute to central manifestations of various diseases. After short-lasting peripheral and neurogenic inflammation, the evidence is mixed whether there are consistent blood-spinal cord changes. In the current study, we examine changes in the blood-spinal cord barrier after intraplantar capsaicin and λ-carrageenan using several methods: changes in occludin protein, immunoglobulin G accumulation, and fluorescent dye penetration. We also examine potential sex differences in male and female adult rats. Results After peripheral carrageenan inflammation, but not capsaicin inflammation, immunohistochemistry shows occludin protein in lumbar spinal cord to be significantly altered at 72 hours post-injection. In addition, there is also significant immunoglobulin G detected in lumbar and thoracic spinal cord at this timepoint in both male and female rats. However, acute administration of sodium fluorescein or Evans Blue dyes is not detected in the parenchyma at this timepoint. Conclusions Our results show that carrageenan inflammation induces changes in tight junction protein and immunoglobulin G accumulation, but these may not be indicative of a blood-spinal cord barrier breakdown. These changes appear transiently after peak nociception and may be indicative of reversible pathology that resolves together with inflammation.